RepEx: A web server to extract sequence repeats from protein and DNA sequences. (February 2019) - Michael, Daliah; Gurusaran, M.; Santhosh, R.; Hussain, Md. Khaja; Satheesh, S.N.; Suhan, S.; Sivaranjan, P.; Jaiswal, Akanksha; Sekar, K.
Abstract: Evolution builds up new genetic material from existing ones, not in random, but in highly ordered and eloquent patterns. Most of these sequence repeats are revelatory of valuable information contributing to areas of disease research and function of macromolecules, to name a few. In the age of next generation genome sequencing, rapid and efficient extraction of all unbiased sequence repeats from macromolecules is the need of the hour. In view of this reckoning, an online web-based computing server, RepEx, has been developed to extract and display all possible repeats for DNA and protein sequences. Apart from exact or identical repeats, the server has been designed adeptly to identify and extract degenerate, inverted, everted and mirror repeats from both DNA and protein sequences. The server has striking output displays, featuring interactive graphs and comprehensive output files. In addition, RepEx has been accoutered with an easy-to-use interface and search filters to facilitate a user-defined query or search and is freely available and accessible via the World Wide Web athttp://bioserver2.physics.iisc.ac.in/RepEx/ .